Factors Associated with Child Health Card Holding among Mothers of Western Rural Nepal: A Cross Sectional Community Based Study - Bhandari, Ramjee; Adhikari, Mandira; Khanal, Vishnu (International Journal of Child Health and Nutrition, 2013)
The use of Child Health Card (CHC) has been found effective to assess overall health status of children worldwide. The tool is simple, cost-effective and easy to use yet standard enough to interpret. Nepal recently made contextual modifications in 2006 and has incorporated it into the Health Management Information System. The card is issued to all children during their first visit for immunization. In Nepal, CHC is considered a valid and authentic report for immunization but little has been studied about its holding. The use of Child Health Card (CHC) has been found effective to assess overall health status of children worldwide. The tool is simple, cost-effective and easy to use yet standard enough to interpret. Nepal recently made contextual modifications in 2006 and has incorporated it into the Health Management Information System. The card is issued to all children during their first visit for immunization. In Nepal, CHC is considered a valid and authentic report for immunization but little has been studied about its holding. The objective of our study was to find its retention rate along with the factors associated. A community-based cross-sectional study was carried out in 10 village development committees of Kapilvastu district between November 15 and December 15, 2010. A total of 190 households were selected using lot quality assurance sampling technique. Higher retention rate (88.9%) of CHC was found while status of complete immunization was significantly associated with its retention [adjusted OR: 41.92, (95%CI; 2.66-658), p=0.008] after adjusting for growth monitoring, ethnicity, place of delivery, antenatal visit, breastfeeding and mother’s age. This study can guide the health system and the family members the measures to sustain higher coverage and retention of CHC which can further guide to the best possible health outcomes for the child.